Transforming China : Insights from the Japanese Experience of the 1980s - N'Diaye, Papa (IMF Working Papers; Working Paper ;, 2010)
China is poised on the brink of a transition to a service-based economy. The Japanese experience of the 1980s provides several insights about the way to manage such a transition and the downsides to avoid. In particular Japan offers useful insights on (1) the limits to an export-oriented growth strategy; (2) the role of exchange rate, macroeconomic policies, and structural reforms in rebalancing the economy toward the nontradables sector; and (3) the risks associated with financial liberalization. The similarities between the Chinese economy today and the Japanese economy of the 1980s make these insights relevant for China. However, with the benefit of analyzing the Japanese experience and, given the important differences between the two economies, China should be able to successfully rebalance its growth pattern while avoiding the downsides encountered by Japan.